The impact of weather on local government spending - Bo Zhao (Federal Reserve Bank of Boston, 2022)
While there is a new and rapidly growing literature on the effects of climatic factors on economic and social outcomes, little research has been conducted to understand the fiscal impact of weather, especially at the sub-state level. Using data from Massachusetts municipalities from 1990 through 2019, this paper estimates government spending as a function of temperature and precipitation while controlling for municipality and year fixed effects and municipality-specific time trends. The results show that weather has statistically significant and economically meaningful effects on local government spending. A 1 degree Fahrenheit increase in the average temperature results in a 3.2 percent increase in real per capita total general fund expenditures. Some government functions, such as public works and general government, are affected more by weather than others. The impact of weather may be persistent and heterogeneous across municipalities. There is some evidence that municipalities adapt to rising temperatures over time.
Keywords: H72; Q51; Q54; 330; weather; climate; local government spending